Evaluation of the food effect on a drospirenone only contraceptive containing 4 mg administered with and without high-fat breakfast in a randomised trial - P.-A. Regidor; W. H. Richter; R. Koytchev; V. Kirkov; E. Colli (BMC, 2022)
Abstract Background The objective of the present trial was to assess the difference in pharmacokinetics (PK) of an oral test preparation containing 4 mg drospirenone (DRSP) under fasting conditions compared to PK upon food intake after single dose administration. Methods Open label, single centre, two-treatment, two-sequence, crossover study in 24 healthy female volunteers, with duration of 1 day per sequence and with a real wash-out period of 14 days to investigate the relative bioavailability of DRSP with both forms of administration. The 90% confidence intervals (CI) were calculated for the intra-individual ratio (test with food vs. without food) of the PK endpoints Area under the curve; 0-72 h [AUC(0-72 h)] and maximal plasma concentration [Cmax] of DRSP. Results The 90% CI calculated by analysis of variance using logistic transformation (ANOVA-log) for the endpoint, intra-individual ratio (Test 'A' = with food intake) vs. Test 'B' = without food intake) of AUC(0-72 h) of drospirenone was between 104.72 and 111.36%. The 90% CI calculated by means of ANOVA- log for the endpoint intra-individual ratio (Test 'A' vs. Test 'B') of Cmax of DRSP was between 118.58 and 141.10%. The mean relative bioavailability of the test with food 'A' compared to the Test without food 'B' after single dose administration based on the endpoints AUC(0-72 h) was 107.99%; for the endpoint Cmax it was 129.35%. Conclusions The rate of absorption, based on the endpoint Cmax of DRSP was increased by about 30% under fed conditions. With respect to consumer habits, this may represent a relevant benefit for contraceptive safety, as the time span between food consumption and pill intake does not play a role. Implications Our results suggest that the food intake has no impact on the absorption of 4 mg DRSP in the management of contraception. This increases the contraceptive efficacy as no interference with food is expected when consuming the oral formulation under real life conditions. Trail registration: Trial registration number: EudraCT-No: 2012-004,309-28.